Comparison between pars plana and anterior endoscopic cyclophotocoagulation for the treatment of glaucoma. (9th May 2019) - Feinstein, Max A.; Lee, Jun H.; Amoozgar, Behzad; Liu, Kelsey; Stewart, Jay M.; Lazcano‐Gomez, Gabriel; Porco, Travis; Han, Ying
Abstract: Importance: This is the first study to compare the efficacy and safety of endocyclophotocoagulation (ECP) via pars plana (ECP‐plus) with ECP via limbus (anterior ECP) for treating glaucoma. Background: There is no direct comparison of treatment outcomes between ECP‐plus and anterior ECP. Design: Retrospective study. Participants: Fifty‐four consecutive patients. Methods: Fifty‐eight eyes from 54 consecutive patients underwent anterior ECP (33 eyes) or ECP‐plus (25 eyes) with 2‐year follow‐up. Linear mixed model was used to analyse the surgical outcomes. Main Outcome Measures: Intraocular Pressure (IOP) was the primary outcome. Secondary outcomes were best‐corrected visual acuity, number of glaucoma medications, complications and success rate. Results: Compared to anterior ECP, patients in the ECP‐plus group had lower IOP (estimate of effect size [EES] = −3.7 mmHg, P  = 0.023) and used fewer number of glaucoma medications (EES = −1.11, P  = 0.003), after adjusting for degrees of treatment, preoperative IOP, and presence of combined ECP and phacoemulsification procedure. Patients with ECP‐plus achieved a higher success rate at 2 years postoperatively (80% vs 33.3%, P  < 0.001). The decrease in IOP between the preoperative and last follow‐up visit was greater in the ECP‐plus group compared to the anterior ECP group (14.3 mmHg (52%) vs 5.2 mmHg (24%), P = 0.001). There was no significant difference in complication rates between the two groups (28% vs 33%, P  = 0.561). Conclusions and Relevance: Anterior ECP and ECP‐plus have a similar safety profile, and ECP‐plus may offer superior IOP control for the management of glaucoma.